Gitar Klasik Lampung Pesisir: Pola Permainan dan Sistem Penalaannya - Erizal Barnawi; Bian Pamungkas; M. Randi Dimas Prayoga; M Yoga (Institut Seni Indonesia Denpasar, 2021)
Purpose: This study aims to find out what songs (tetti') are on the Lampung Coastal Classical Guitar and to be able to be transcribed into beam notation. Because so far not many have transcribed to become learning materials. Research methods: Qualitative research with a case study approach is applied and a musicological analysis study will be used to analyze the passages and the tuning system on the Lampung Coastal Classical Guitar. Results and discussion: The results of the reduction were analyzed based on the theoretical framework used by Alan P Marriam's concept to determine the tuning and strumming system used by Edi Pulampas, Hila Hambala, and Imam Rojali. The results of the analysis will be related to the framework of Karl Edmund Prier SJ's thinking about a form of Lampung Coastal Classical Guitar music that exists and lives in the community. Implication: The names of the tunings found in the study are the Salimpat Stem, Gung Sai Stem, Triple Stem, Batang Hari Sembilan Stem and Standard Stem. With the tuning system, Salimpat Stem (e',b,fis,d,b,E), Gung Sai Stem (e',b,g,d,b,E), Triple Triumvirate Stem (e',b,e', d,b,E), Nine Days Stem (e',b,fis,d,b,E) and standard stem (e',b,g,d,a,E).